2005
DOI: 10.1016/j.jcrs.2004.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Medical control of intraocular pressure after phacoemulsification

Abstract: Brinzolamide was as effective as acetazolamide in preventing IOP elevation 4 to 6 hours after phacoemulsification and more effective than acetazolamide at 18 to 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 15 publications
(9 reference statements)
0
30
1
6
Order By: Relevance
“…[20][21][22][23] In our study, the effectiveness of dorzolamide-timolol maleate combination was not different from that of oral acetazolamide.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…[20][21][22][23] In our study, the effectiveness of dorzolamide-timolol maleate combination was not different from that of oral acetazolamide.…”
Section: Discussioncontrasting
confidence: 40%
“…There was no statistically significant difference between two groups (p=0.924). The mean postoperative IOP (1 st day) of the first group was 15.27±2.90 (SD) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) mmHg and that of the second group was 14.82±2.57 (SD) (11-23) mmHg. There was no statistically significant difference between two groups (p=0.505).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hipertensão ocular é uma complicação reconhecida após cirurgia de catarata, mesmo quando realizada sem complicações ou intercorrências per-operatórias (10,11) . A diminuição das propriedades biomecânicas da córnea está relacionada a dificuldade na capacidade de detectar o aumento da PIO (12,14) .…”
Section: Discussionunclassified
“…1,4 The problem with the vast majority of the studies that have investigated prophylaxis regimes for a raised IOP is that they have excluded patients suffering with glaucoma or OHT. [8][9][10][11][12][13][14][15][16][17][18][19] It is of importance to study such regimes specifically in glaucoma and OHT populations, as it is these patients who are most at risk of a raised IOP. 6,12,20 It has been suggested that this pressure rise may be transient postoperatively.…”
Section: Introductionmentioning
confidence: 99%